Student Formative Process in Mathematics: digital games and Parkinson's treatment - Azevedo, Greiton Toledo; Maltempi, Marcus Vinicius; Lyra-Silva, Gene Gene Maria Vieira (Universidade Estadual de Campinas, 2018)
This work seeks to understand the formative process of Basic Education students in addition to the usual math classroom practices, involving the production of digital games and their use with Parkinson's patients. This initiative was carried out within the Mathematics Extension Project of the Goiano Federal Institute, Advanced Ipameri Campus, in a public school in the metropolitan region of Goiania, guided by qualitative research. The data produced were analyzed from elements of the Construction and Learning Turbulence identified in the activities mobilized beyond the social and human aspects fabricated throughout the student's formation. The results obtained with the data analysis indicate elements of the created environment that act as context and motor for the production of meanings in mathematics by the students, evidencing the relevance of a contextualized and active formation.